2017
DOI: 10.3762/bjnano.8.193
|View full text |Cite
|
Sign up to set email alerts
|

Freestanding graphene/MnO2 cathodes for Li-ion batteries

Abstract: Different polymorphs of MnO2 (α-, β-, and γ-) were produced by microwave hydrothermal synthesis, and graphene oxide (GO) nanosheets were prepared by oxidation of graphite using a modified Hummers’ method. Freestanding graphene/MnO2 cathodes were manufactured through a vacuum filtration process. The structure of the graphene/MnO2 nanocomposites was characterized using X-ray diffraction (XRD) and Raman spectroscopy. The surface and cross-sectional morphologies of freestanding cathodes were investigated by scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…The first cycle charge delivered a capacity of 540 mAh/g (Figure a). The observed differences in first cycle charge and discharge capacity for cathode materials are not expected but have been observed previously. However, this observation is rarely discussed. Sometimes, the first cycle charge–discharge capacity or all charge capacity are omitted in the capacity versus number cycle plots in the literature. Here, we would like to propose plausible explanations.…”
Section: Results and Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The first cycle charge delivered a capacity of 540 mAh/g (Figure a). The observed differences in first cycle charge and discharge capacity for cathode materials are not expected but have been observed previously. However, this observation is rarely discussed. Sometimes, the first cycle charge–discharge capacity or all charge capacity are omitted in the capacity versus number cycle plots in the literature. Here, we would like to propose plausible explanations.…”
Section: Results and Discussionmentioning
confidence: 51%
“…The observed differences in first cycle charge and discharge capacity for cathode materials are not expected but have been observed previously. However, this observation is rarely discussed. Sometimes, the first cycle charge–discharge capacity or all charge capacity are omitted in the capacity versus number cycle plots in the literature. Here, we would like to propose plausible explanations. One of the possible reasons of the observed difference in first cycle could be attributed accident partial discharge in cell assembly process before testing, since the cells were assembled in the charged state.…”
Section: Results and Discussionmentioning
confidence: 51%
“…After the redox chemical reaction step, peaks associated with the crystallinity of MnO 2 did not appear in the MnO 2 -PPy@PAN, whereas in the β-MnO 2 @CNF spectrum, characteristic diffraction peaks at 2θ angles of 34.98, 40.60, and 58.72° corresponding to the (110), (101), and (211) planes of β-MnO 2 were observed. , In addition, Figure b exhibits Raman spectra in the range 200–2500 cm –1 of the CNF sheets without and with MnO 2 decoration. The typical β-MnO 2 peaks at 650 cm –1 indicate the stretching mode of octahedral MnO 6 , and two weak peaks at 362 and 302 cm –1 originate from the bending mode of O–Mn–O or Mn 3 O 4 as a minor portion of Mn 2 O 3 . , Energy-dispersive X-ray spectroscopy (EDX) element mapping analysis also confirmed that Mn and N were uniformly distributed along the surface of an individual nanofiber in the sheet structure (Figure ).…”
Section: Resultsmentioning
confidence: 94%
“…2, the diffraction peaks of the pure β-MnO 2 were at 28.6°, 37.3°, 40.9°, 42.8°, 46.1°, 56.7°, 59.4°, 64.8°, 66.8°, 67.3° and 72.3°, corresponding to (110), (101), (200), (111), (210), (211), (220), (002), (310), and (112) planes, respectively. 58–60 There were no other peaks that resembled different phases or impurities. The XRD pattern of β-MnO 2 /CNTs closely resembled the β-MnO 2 reference spectrum.…”
Section: Resultsmentioning
confidence: 99%